Collegiate rugby union injury patterns in New England: a prospective cohort study. Issue 7 (18th January 2008) - Kerr, H A; Curtis, C; Micheli, L J; Kocher, M S; Zurakowski, D; Kemp, S P T; Brooks, J H M
Abstract : Objective: To establish injury profile of collegiate rugby union in the USA Design/setting: 31 men's and 38 women's collegiate rugby union teams prospectively recorded injuries during games and practice during the 2005–06 season. Three teams withdrew before data collection. An injury was defined as one: (1) occurring in an organised intercollegiate game or practice; and (2) requiring medical attention during or after the game or practice, or (3) resulting in any restriction of the athletes' participation for ⩾1 day(s) beyond the day of injury, or in a dental injury. Main outcome measures: In total, 847 injuries (447 in men; 400 in women) during 48 026 practice (24 280 in men; 23 746 in women) and 25 808 game (13 943 in men; 11 865 in women) exposures were recorded. Results: During games, injury rates of 22.5 (95% CI 20.2 to 25.0) and 22.7 (20.2 to 25.5) per 1000 game athletic exposures or 16.9 (15.1 to 18.9) and 17.1 (15.1 to 19.1) per 1000 player game hours were recorded for men and women, respectively. Over half of all match injuries were of major severity (>7 days' absence) (men 56%; women 51%) and the tackle was the game event most often associated with injury (men 48%; women 53%). Conclusions: Collegiate game injury rates for rugby were lower than rates recorded previously in men's professional club and international rugby and lower than reported by the National Collegiate Athletic Association Injury Surveillance System for American football, but similar to rates reported for men's and women's soccer in 2005–06.